Micrografts for mega jujube trees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
With a variety of uses in dry areas, the jujube tree (Ziziphus mauritania Lam.) is always a candidate for propagation, and now micrografting techniques are offering prospects of massive production.